A subsystem model of monitoring intsedent of information security in information systems of organizations - Пількевич, Ігор Анатолійович; Котков, Володимир Іванович; Лобанчикова, Надія Миколаївна; Сугоняк, Інна Іванівна (Eastern-European Journal of Enterprise Technologies, 2012)
A formalization of the problem of monitoring the information security system to identify the incidents in the information system of organization using a systematic approach is presented in this work